A Complete Fisheries Inventory of the Chulitna River Basin, Lake Clark National Park and Preserve, Alaska: Example of a Minimally Disturbed Basin. Issue 1 (13th January 2020) - Hughes, Robert M.; Boxall, George; Herlihy, Alan T.; Adams, Jason; Young, Daniel B.
Abstract: Because of mineral mining threats in the headwaters that drain into Lake Clark National Park, we implemented a baseline ecological survey of the Chulitna River basin through the use of a probability study design. A total of 49 wadeable stream and raftable river sites were sampled for fish assemblages, multiple physical habitat structure variables, and multimeter chemistry (dissolved oxygen, conductivity, pH, and water temperature) by the using standard methods that are employed in the United States Environmental Protection Agency's (USEPA) National Rivers and Streams Assessment. We recorded moderate levels of canopy density, low levels of riparian woody vegetation cover, and the absence of large wood in the Chulitna River basin streams. The extremely low levels of channel incision, the absence of riparian anthropogenic disturbance, and high levels of water quality indicate insignificant anthropogenic landscape alteration in these streams and rivers. Fish were not observed at seven sites, representing 27% of the calculated 2, 220 km of the target stream length in the study population. Arctic Grayling Thymallus arcticus, Dolly Varden Salvelinus malma, and Northern Pike Esox lucius were present in 10% (227 km), 38% (847 km), and 8% (181 km) of the calculated target stream/river length, respectively. The most commonly occurring and abundant species, Slimy Sculpin Cottus cognatus (now Uranidea cognata ), was present in 56% (1, 244 km) of the calculated stream/river length. The lack of anadromous salmon detections was associated with salmonid life histories, naturally high levels of substrate fines and embeddedness, and the presence of Northern Pike. The quality of physical habitat and water quality, as well as the occurrences of Arctic Grayling and Dolly Varden, are representative of the unimpaired waters in Alaska, compared with those in the conterminous USA. We concluded that statistically and ecologically rigorous stream and river sampling can be implemented across a roadless region at reasonable cost and with sufficient planning.